Analysis of Online Based Learning on Teacher Professionalism in Elementary School during the COVID-19 Pandemic - Priatna, Yundara Ulfa; Rahman, Rahman (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2021)
The implementation of online-based learning as an impact of COVID-19 in Indonesia is the background for this study. This study aims to determine the effect of online-based learning on teacher professionalism in elementary schools. This study uses a qualitative descriptive method. The instrument used a questionnaire using google form. The population in this study were teachers in elementary schools. The sample in this study was 31 respondents. Based on data, it was found that teachers were able to master learning material in online learning, master competency standards, and basic competencies of subjects in online learning, to develop professionalism sustainably by taking reflective action. However, teachers have difficulties in developing learning materials creatively and utilizing information and communication technology in self-development in online learning. The obstacles that are felt by the teacher are the habit of face-to-face learning, school locations in rural areas have more difficulties in term of connection compared to urban areas, the teacher cannot directly control the student development process so that assessment is only carried out based on the assignments that have been collected only, not from daily activities